Between the academy and the market where communication and marketing are found: a case study of the Petrogas/Se Network (Comunicação & Inovação, 2018)
This paper proposes a discussion on the connection between organizational communication and marketing and the perceived gap between academic theory and market practice. Companies participating in the Petrogas Network of Sergipe were observed. The holistic single-case study methodology proposed by Yin was used. Through this study it can be seen that, even in light of the rigid methods proposed by international standards, both communication and marketing have been neglected in the companies analyzed.
Keywords: Organizational communication. Marketing. Integrated marketing communication.